Pharmacological Activity and Effectiveness of Electrohomoeopathy Medicine on Uterine Fibroids Individuals - Pandey, Dr. Surendra; Singh, Dr. Harvinder (International Journal of Innovative Research in Medical Science, 2021)
Electropathy/Electrohomoeopathy is a comparatively modern medical technique that falls under the genre of complementary and alternative medicine. This medical technique was discovered in Italy in 1865 by Count Ceaser Mattei. Its drugs are composed entirely of herbal/medicinal plants and are manufactured with purified water and a sophisticated process of extracting spagiric essence from medicinal plants at room temperature. Uterine fibroids are noncancerous uterine growths that commonly arise during childbearing year. Uterine fibroids, also known as leiomyomas (lie-o-my-O-muhs) or myomas, aren't linked to an increased risk of uterine cancer and almost never turn cancerous. Fibroids range in size from microscopic seedlings that are undetectable to large masses that deform and expand the uterus. A single fibroid or a group of them can be present. Multiple fibroids can cause the uterus to enlarge to the point where it reaches the rib cage, causing weight gain. Uterine fibroids affect many women at some point in their life. However, because uterine fibroids rarely cause symptoms, people may be unaware that they have them. During a pelvic exam or a pregnancy ultrasound, fibroids may be encounter by chance. By the time they reach at the age 50, 20% to 80% of women experience fibroids. Women in their age forties and early fifties are the most susceptible to develop get fibroids. In this article we are going to discussed effectiveness of Electrohomoeopathy medicine on Uterine fibroids. How a new medical science which is totally plants-based source cost effective and accelerating its mechanism of action due to specialization of its unique fundamental principal and philosophy and satisfaction of patient due to the extraordinary result of Electrohomoeopathy medicine.